2012
DOI: 10.1111/j.1399-3062.2012.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis jirovecii pneumonia 13 years post renal transplant following a recurrent cytomegalovirus infection

Abstract: Pneumocystis jirovecii (formerly Pneumocystis carinii) pneumonia (PCP) is a rare but serious infection that usually occurs within a year after solid organ transplantation. PCP may occur after 1 year post transplantation, but the rate is reported to be very low. Studies have shown an association between cytomegalovirus (CMV) infection in solid organ transplant patients and an increased risk of opportunistic infection. This increased risk is thought to be a result of the immunomodulatory effects of the CMV infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Finally, we observed an increased incidence of pneumocystis and pulmonary aspergillosis among cases. This observation has been documented in previous reports( 26 , 27 ) and can be the result of an immunosuppressive state induced by CMV infection. The retrospective nature of our data precluded further investigation of this hypothesis.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, we observed an increased incidence of pneumocystis and pulmonary aspergillosis among cases. This observation has been documented in previous reports( 26 , 27 ) and can be the result of an immunosuppressive state induced by CMV infection. The retrospective nature of our data precluded further investigation of this hypothesis.…”
Section: Discussionsupporting
confidence: 85%
“…Some single‐center studies showed pneumocystis pneumonia (PCP) is a rare disease in SOT recipients and casted doubt on the requirement for prophylaxis . However, in our study, 12% of IFI episodes were pneumocystis pneumonia (PCP).…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with that of previous studies 17, 21 . CMV is known to modify host immune responses by various mechanisms, suppressing helper T-cell and antigen presenting cell functions 22 . Therefore, CMV infection is both a marker of an immunocompromised state and has, itself, an immunosuppressive effect 23 .…”
Section: Discussionmentioning
confidence: 99%